Intrathoracic ganglioneuroma presenting as an endobronchial mass. (2017) - Nokes, Brandon T.; Baumann, Coralie P.; Cummings, Kristopher W.; Larsen, Brandon T.; Cartin-Ceba, Rodrigo; Swanson, Karen L.
Abstract: Peripheral nerve sheath tumors (PNST) are exceedingly rare, especially outside of the posterior mediastinum. These tumors represent less than 1% of pulmonary tumors. Very few pulmonary PNSTs are ganglioneuromas. We present a case of a ganglioneuroma presenting as an endobronchial mass. Case presentation: An 80 year old male was seen in pulmonary clinic for routine cancer screening. He had a 60-pack year smoking history. CT evaluation noted a 1cm right lower lobe endobronchial lesion. This lesion was present since 2012 and had slightly increased in size since that time from 8mm (Figure 1). The lesion was further assessed using virtual bronchoscopy (Figure 2). Bronchoscopy revealed an obstructing lesion, which was completely excised with the snare (Figure 3). Pathology revealed well-circumscribed tumor consisting of nests and trabeculae of round/polygonal cells with granular eosinophilic and basophilic cytoplasm. The tumor was chromogranin, synaptophysin, S-100, pancytokeratin, SOX10, and TTF-1 positive, consistent with a ganglioneuroma. Discussion: Aside from a solitary article regarding 75 patient samples (which included only one ganglioneuroma) only a small number of intrathoracic PNSTs have been reported. Only a single case report of an endobronchial ganglioneuroma has been reported. Each of these lesions were benign, and detected on routine imaging evaluations. Conclusions: An intrapulmonary endobronchial location for a PNST is an exceedingly rare presentation of an already uncommon pathology.